The obligation to provide a technical opinion on the budgetary, financial, and actuarial impacts of bills that amend legislation about Social Security System for Public Servants - Queiroz, Carla Ferreira Lopes da Silva; Gomes, Patricia Ribeiro Silva; Dias, Milena Guilherme (Seven Editora, 2023)
The object of this study is about the obligation of the technical opinion on the budgetary, financial, and actuarial impacts of bills that change the legislation of the RPPS. Can the legal provision in the local rules that regulate the RPPS to oblige the preparation of a technical opinion detailing the various aspects of the RPPS expenses, both in the present and in the future, be a measure that provides efficient and sustainable management practices? This is the chosen problem. The affirmative hypothesis points to the possibility of developing another tool that adjusts the financial and actuarial balance of the RPPS to the nature of a social security system that should ordinarily make use of the direct sources of funding, that is, the employers' and insured contributions. The negative hypothesis, on the other hand, alerts to the scenario of discretion of the competent authority to decide based on the technical opinion or not, and the political interferences that predominate over the technical factors. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-149